THE INFLUENCE OF PROBLEM BASED INSTRUCTION (PBI) COOPERATIVE LEARNING MODELS ON MATHEMATICAL CREATIVE THINKING ABILITY VOCATIONAL STUDENTS - Cut Indah Lestari (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2023)
One of the problems in learning mathematics is the opinion of the majority of vocational school students that mathematics is a difficult and boring subject. One alternative that is assumed to be able to overcome this problem is to apply the Problem Based Instruction (PBI) learning model to students' mathematical creative thinking abilities as an effort to improve their ability to think and solve problems with many ideas, producing various ideas, which can creating new ways that have nothing in common with others and being able to develop an idea. This research aims to determine students' mathematical creative thinking ability scores and the influence of PBI learning on students' mathematical creative thinking abilities in vocational schools. This research uses a quantitative approach with experimental methods. The population in this study were all class Data was collected through a pretest and posttest in the form of a description test and given to students before and after learning using the PBI model. Next, the data was analyzed using the Wilxocon test via SPSS. The results of the research show that students' creative thinking abilities in matrix material are in the good category with an average of 74.5%. Based on calculations in the Willcoxon test, it was found that the significant value of each variable was less than 0.05, namely 0.000 0.05, so it was rejected and accepted. As a result, it can be concluded that there is an influence of the use of the Problem Based Instruction (PBI) cooperative learning model on vocational school students' mathematical creative thinking abilities on matrix material. Keywords: PBI Learning, Mathematical Creative Thinking Ability